1969
DOI: 10.1287/mnsc.16.2.b61
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reducing Leadtime on Inventory Levels-Simulation Analysis

Abstract: The allowed safety stock level reduction and accompanying reduction in average on-shelf inventory level are evaluated, for prescribed system performance requirements, as a function of mean leadtime reduction. The general simulation technique developed for this purpose allows the treatment of the s, S periodic review inventory problem with both demands and leadtime being stochastic. Some results obtained for a military supply system, where the reduction in leadtime is achieved by resorting to airlift rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…8 Also, research has found that for high service level re q u i rements, re d u c i n g lead time reduces expected inventory levels. 9 Thus, lead time effects were avoided by treating them as fixed.…”
Section: Methodsmentioning
confidence: 99%
“…8 Also, research has found that for high service level re q u i rements, re d u c i n g lead time reduces expected inventory levels. 9 Thus, lead time effects were avoided by treating them as fixed.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Gross (1969) evaluates change in inventory resulting from reduced mean lead time using simulation. Ebrahimpour (1985) uses simulation to investigate claims that Kanban systems result in less Work in Process inventory.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers on LTR in the literatures focused on the relation between lead-time and stock level, such as Donald Gross [5], Tyworth et al [6], Glasserman et al [7], Chen et al [8], little is on effect on the expected profits of both supply chain parties. Iyer and Bergen (1997) [9] applied bayesian methodology to study how a manufacture-retailer channel impacts choice of production and marketing variables under QR (Quick Response) in the apparel industry, but the quantitative relations between lead time and expected profits and the effect of LTR on the s u p p l y c h a i n c h a n n e l a r e n ' t e m b e d d e d i n t o their works.…”
Section: Introductionmentioning
confidence: 99%